Seeding and Acclimatization for Aerobic Processing of Restaurant Wastewater with Sequencing Batch Reactor - Herawati Budiastuti; Laily Isna Ramadhani; Sudrajat Harris Abdulloh; Ananda Dea Maharani; Melina Melina; Robby Sudarman (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Restaurant wastewater has a relatively high organic matter content, so it needs to be treated to meet the specified quality standard. One of the technologies that can be used in restaurant wastewater treatment is Sequencing Batch Reactor (SBR) technology. The purpose of this study is to set up an aerobic SBR system with seeding and acclimatization treatments to reduce the amount of organic matter in restaurant wastewater when a shock load occurs. The research was done using wastewater from a restaurant in Bandung and activated sludge from the food industry in Bogor as seeds for microorganisms. In this study, the seeding process was carried out by introducing 25% activated sludge and 75% nutrients into the reactor, and the acclimatization process was carried out by introducing a specific ratio of nutrients and wastewater into the reactor gradually until the waste concentration reached 100%. The parameters tested were COD, MLVSS, DO, pH, and temperature. During the seeding procedure, the initial COD value of 3,200 mg/L declined. It began to stabilize on the seventh day, with a COD value of 1,080 mg/L. The COD removal reached a relatively stable condition in the acclimatization process starting on day 2, where COD decreased from the original 1,280 mg/L to 480 mg/L.